NEW DATA ABOUT THE DISTRIBUTION OF ANOMALOUS BLUE POLYOMMATUS ADMETUS (ESPER, 1783) (LEPIDOPTERA: LYCAENIDAE) IN CROATIA (Acta Entomologica Serbica, 2010)
decade, however, much new data about the butterflies of Croatia was published, including the finding of several new species for Croatia and the expansion of the known area of distribution for some rare species. Still some species that were recorded almost a hundred years ago in Croatia have not been found since. During the field trips taken in 2009 and 2010 in middle Dalmatia, a rare butterfly species, Anomalous Blue Polyommatus admetus (Esper, 1783), was recorded in several new locations around the Cetina and Zrmanja Rivers. These are the first records of the species in Croatia since the beginning of the 20th century. The known range of the species in Croatia is vastly expanded, although possibly still incomplete.